104 The Relationship Between Site-Specific Prostate Surface Dose in Cases of Iodine-125 Prostate Brachytherapy and Erectile Dysfunction. (1st May 2022) - Ishii, S; Takata, R; Kikuchi, K; Itoh, A; Tsuyukubo, T; Tamura, D; Ikarashi, D; Maekawa, S; Matsuura, T; Kato, R; Kato, Y; Kanehira, M; et al.
ABSTRACT: Objective: To conduct detailed measurements of site-specific radiation doses in 36 sections plotted on the surface of the prostate after brachytherapy (BT), to conduct a comprehensive analysis of the regions associated with erectile dysfunction (ED). Subjects and methods: The subjects were 81 patients selected from among patients who underwent BT between 2004 and 2016 because they were able to complete the International Index of Erectile Function (IIEF)-6 questionnaire pre-treatment and 12 months post-treatment. Post-planning was done by inputting CT images made over a four-week period after treatment into a radiotherapy planning system, dividing the surface of the prostate into 36 equal sections, and measuring the D90 radiation dose (Gy) at each site. The soft tissue surrounding the corpus cavernosum was set as the ROI for the uretheral bulb spongy tissue, and the radiation dose to this region was similarly calculated. Results: We selected 56 of the 81 patients who did not have ED or who had mild ED prior to treatment. 23 patients who scored 22 or higher on the IIEF-6 at 12 months post-treatment were assigned to the non-ED group, and 11 patients who scored under 11 were assigned to the ED group. Statistical inter-group comparison of the site-specific radiation doses indicated that the doses were significantly higher in the ED group in the following sections: Center of right lobe at 3 o'clock, center of left lobe at 2-4 o'clock, apex of left lobe at 2-4 o'clock. No significant difference in radiation dose was found for the corpus cavernosum. Conclusion: In the group of patients with high radiation doses to the middle and apex at 2 – 4 o'clock the IIEF-6 score was significantly lower at 12 months post-treatment. This suggests that excessive radiation exposure to these sections may have an effect on post-BT ED. Disclosure: Work supported by industry: no.